Growth Mindset Leadership and Employee Performance: Evidence from Cambodia’s Emerging Economy - Bora Khath; Chamab Voeun (Srawung: Journal of Social Sciences and Humanities, 2026)
This study examines the impact of growth mindset leadership on employee performance among working professionals in Cambodia. Leadership plays a crucial role in shaping employee behavior and organizational outcomes, particularly in dynamic and competitive environments. However, limited research has explored how leaders’ mindset orientations influence employee performance in emerging economies. This study aims to address this gap by investigating whether growth mindset leadership enhances employee performance. A quantitative research design was employed, and data were collected from 61 working professionals across multiple sectors. The data were analyzed using correlation and regression analysis. The findings show that growth mindset leadership has a positive and statistically significant association with employee performance, explaining 49.1% of the variance (R² = 0.491). This study contributes by applying growth mindset theory to leadership research in an emerging economy context. These results indicate that leaders who emphasize learning, development, and continuous improvement can significantly improve employee effectiveness. This study contributes to the literature by applying growth mindset theory  to leadership research in an emerging economy context and providing empirical evidence from Cambodia. The findings also offer practical implications for organizations seeking to enhance performance through leadership development.